2012
DOI: 10.1590/s0034-737x2012000400020
|View full text |Cite
|
Sign up to set email alerts
|

Biomassa microbiana e matéria orgânica em solo de Caatinga, cultivado com melão na Chapada do Apodi, Ceará

Abstract: Microbial biomass and organic matter in soil of Caatinga, cultivated with melon in Chapada do Apodi, Ceará StateThe intensive use of the conventional system over the years of soil preparation may change the soil microbial attributes, causing a reduction of biomass and microbial activity. As so, the present study aimed to analyze, under melon (Cucumis melo L.) cultivation, the microbiological changes as well as soil organic matter content in the depth of 0-0.10, 0.10-0.20, 0.20-0.30 and 0.30-0.40 O uso contín… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
2
0
4
Order By: Relevance
“…Soil physical attributes showed higher Ds values at the three studied depths in the soil with Caatinga; the area with onion showed the highest values among the evaluated production systems (Table 3). Lopes et al (2012) verified higher values of soil density in the surface soil layer of the Caatinga area, which was attributed to the presence of crop residues in this area.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Soil physical attributes showed higher Ds values at the three studied depths in the soil with Caatinga; the area with onion showed the highest values among the evaluated production systems (Table 3). Lopes et al (2012) verified higher values of soil density in the surface soil layer of the Caatinga area, which was attributed to the presence of crop residues in this area.…”
Section: Resultssupporting
confidence: 61%
“…These authors highlighted Ma as a sensitive attribute for discriminating the physical quality at a depth of 0.00-0.10 and 0.10-0.20 m, while Ds and Mi were more important at a depth of 0.20-0.40 m, thus being considered good soil quality indicators. Lopes et al (2012) observed higher OM values in the surface soil layer of a Caatinga area when compared to an area with melon, which was attributed to the presence of dead coverage in this area as depth decreased. Also, a significant increase in OM was observed at a depth of 0.20-0.40 m when compared to the soil under Caatinga, which is similar to the result obtained in the area with banana of this study.…”
Section: Resultsmentioning
confidence: 73%
“…Os microrganismos do solo e o resultado de sua atividade têm sido apontados como um dos atributos mais sensíveis às alterações na qualidade do solo, causadas por mudanças de uso e práticas de manejo (Lopes et al, 2012). Isto evidencia o efeito das modificações, de forma antecipada, em relação aos demais atributos (Balota et al, 2004).…”
Section: Introductionunclassified
“…(2009), Portugal et al (2010 e Pragana et al (2012), que observaram aumento da densidade do solo com a intensificação do uso. Lopes et al (2012), no entanto, verificaram maiores valores de densidade do solo na camada superficial da área de caatinga, atribuindo esse resultado à presença de cobertura morta nessa área.…”
Section: Comparação De Médias Dos Dados Dos Atributos Físicos Do Solounclassified